2017
DOI: 10.1186/s12862-017-1025-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic variation between urban and rural populations of Darwin’s finches

Abstract: BackgroundThe molecular basis of evolutionary change is assumed to be genetic variation. However, growing evidence suggests that epigenetic mechanisms, such as DNA methylation, may also be involved in rapid adaptation to new environments. An important first step in evaluating this hypothesis is to test for the presence of epigenetic variation between natural populations living under different environmental conditions.ResultsIn the current study we explored variation between populations of Darwin’s finches, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 66 publications
7
56
3
Order By: Relevance
“…This difference in methylation between bold and shy types was not found in a forest population (Riyahi et al 2015). A later study found differences in DNA methylation levels and morphological features between rural and urban populations of Darwin's finches (Geospiza fortis and Geospiza fuliginosa) (McNew et al 2017). In contrast to genetic variation (Bonduriansky and Day 2009;Ledon-Rettig et al 2013;Price et al 2003), epigenetic variation may enable organisms to adjust their phenotype to match novel environments, or provide them with the ability to quickly respond to a changing environment (Jablonka and Lamb 2007;Tammen et al 2013).…”
Section: Human-induced Epigenetic Changesmentioning
confidence: 94%
“…This difference in methylation between bold and shy types was not found in a forest population (Riyahi et al 2015). A later study found differences in DNA methylation levels and morphological features between rural and urban populations of Darwin's finches (Geospiza fortis and Geospiza fuliginosa) (McNew et al 2017). In contrast to genetic variation (Bonduriansky and Day 2009;Ledon-Rettig et al 2013;Price et al 2003), epigenetic variation may enable organisms to adjust their phenotype to match novel environments, or provide them with the ability to quickly respond to a changing environment (Jablonka and Lamb 2007;Tammen et al 2013).…”
Section: Human-induced Epigenetic Changesmentioning
confidence: 94%
“…In our population, both plumage brightness and negative feedback predict stress resilience (Taff et al, , ; Zimmer et al, ), but the two traits are only weakly correlated, further supporting the idea that they might contribute to variation in resilience through different mechanisms. Most prior studies that use a similar MeDIP approach have also focused on categorical traits that might be expected to have large‐scale consequences on methylation throughout the genome, such as urban versus rural populations (McNew et al, ), sister species (Skinner et al, ) and rearing conditions (Pertille et al, ). To our knowledge, no other studies to date have used MeDIP to examine differences in glucocorticoid regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The level of fragmentation and total length of our assembly are similar to the 45 avian genomes published by Zhang et al (), albeit with a slightly shorter scaffold N50. One of these genomes was used by McNew et al () in a MeDIP analysis comparing rural and urban Geospiza fortis individuals. The average and standard deviation for comparable statistics from the Zhang et al () genomes is 1.1 ± 0.1 Gb in length, with N50s of 21.2 ± 7.7 Kb (contig) and 1.7 ± 2.4 Mb (scaffold).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations